KETERAMPILAN KOMUNIKASI EFEKTIF SEKRETARIS SEBAGAI KUNCI PELAYANAN PRIMA DI ERA DIGITAL - Myssiliyana Putri, Anggun; Tri Lestari, Ayu; Damayanti, Ine; Salsabila, Nadjwa; Rifani Yulianti; Rahmaningtyas, Wisudani (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2025)
The development of digital technology requires the role of secretaries to not only master administrative skills, but also effective communication skills as a key in realizing excellent service. This research aims to analyze the role of secretary communication skills in supporting excellent service in the digital era, identify relevant forms of communication skills, and formulate development strategies. The method used is a literature study from various scientific sources such as journals, books, and related articles. The study results show that secretaries are required to have verbal and nonverbal communication skills, mastery of digital technology, interpersonal skills, and sensitivity to context and audience. The main challenges faced include limited digital literacy, lack of ethical communication training, and cross-generational communication gaps. Suggested development strategies include blended learning-based training, cross-generational mentoring, and enhancing adaptive culture in the work environment. The integration of communication skills and technology utilization is the main foundation in creating professional and highly competitive service excellence in the digital era.